Surgical Reconstruction of a Traumatic Superior Sagittal Sinus Injury Using Synthetic Vascular Graft in a Resource-Limited Civilian Field Hospital During the Syrian Civil War - Abdallah, Omar Ibrahim; Clark, David; Essibayi, Muhammed Amir (Elsevier Science Inc, 2022)
penetrating brain injury are rare but are often associated with significant morbidity and mortality. The management of significant defects is operative and can be challenging. In modern civilian practice, patients with these injuries typically receive extensive preoperative investigation and advanced perioperative monitoring. - METHODS: We report a case of successful operative management in a frontline civilian field hospital of a 33year-old man who sustained a shrapnel injury to the junction of the middle and posterior thirds of the superior sagittal sinus during the Syrian Civil War. - RESULTS: The injury was repaired successfully with a polytetrafluoroethylene graft. The postoperative course was uncomplicated. Anticoagulation was commenced 2 days postoperatively. The patient was discharged 5 days postoperatively with a GCS of 15 and mild weakness of the limbs bilaterally. - CONCLUSIONS: Immediate repair of dural sinus injuries is feasible in the context of a low-resource wartime environment and should be attempted without delay. To our knowledge, this is the first case of successful use of a synthetic vascular graft for repair of a dural venous sinus injury in an ill-equipped hospital.
Keywords: Key words Conflict; PTFE graft; Superior sagittal sinus; Superior Syria; Syria Trauma